A Theological Reflection on COVID-19: Suffering Christ and the Paradigm of Discipleship in Mark 9:36-37 - David Kristanto (STFT Jakarta, Indonesia, 2020)
This article seeks to answer the question, “Where is God in the midst of suffering?”, through reflecting on the paradigm of discipleship in Mark 9:36-37. Welcoming a child is a parabolic action done by Christ to show that the way to be the greatest is to welcome the weakest or to be the servant of all. A child is used as a paradigm due to his or her low status in the Greco-Roman society. Children had no right, seen as properties rather than persons, and thus equated to slaves. Therefore, welcoming a child means welcoming the weakest of the society, and doing so means to welcome Christ himself and the one who sent him. The suffering caused by COVID-19 makes the whole world suffer, yet it also creates a bigger gap between the rich and the poor, the strong and the weak. A reflection on the paradigm invites Christians to side with the weakest and those who are in need, hoping that the kingdom of God will be ushered into this suffering world.